NOTCH, ERK, and SHH signaling respectively control the fate determination of cortical glia and olfactory bulb interneurons - Yanjing Gao; Mengge Sun; Tongye Fu; Ziwu Wang; Xin Jiang; Lin Yang; Xiaoyi G. Liang; Guoping Liu; Yu Tian; Feihong Yang; Jialin Li; Zhenmeiyu Li; et al. (Proceedings of the National Academy of Sciences, 2025)
During cortical development, radial glial cells (neural stem cells) initially are neurogenic, generating intermediate progenitor cells that exclusively produce glutamatergic pyramidal neurons. Next, radial glial cells generate tripotential intermediate progenitor cells (Tri-IPCs) that give rise to cortical astrocytes and oligodendrocytes, and olfactory bulb interneurons. The molecular mechanisms underlying the transition from cortical neurogenesis to gliogenesis, and the subsequent fate determination of cortical astrocytes, oligodendrocytes, and olfactory bulb interneurons, remain unclear. Here, we report that extracellular signal-regulated kinase (ERK) signaling plays a fundamental role in promoting cortical gliogenesis and the generation of Tri-IPCs. Additionally, sonic hedgehog-smoothened-glioma-associated oncogene homolog (SHH-SMO-GLI) activator signaling has an auxiliary function to ERK during these processes. We further demonstrate that, from Tri-IPCs, NOTCH signaling is crucial for the fate determination of astrocytes, while ERK signaling plays a prominent role in oligodendrocyte fate specification, and SHH signaling is required for the fate determination of olfactory bulb interneurons. We provide evidence suggesting that this mechanism is conserved in both mice and humans. Finally, we propose a unifying principle of mammalian cortical gliogenesis.